Uncovering hidden diversity: Phylogeny and taxonomy of physoderinae (Reduviidae, heteroptera), with emphasis on Physoderes westwood in the oriental and Australasian Regions - Hwang, W.S (Museum National d'Histoire Naturelle, 2020)
10.5852/ejt.2017.341